Effect of AuPd Bimetal Sensitization on Gas Sensing Performance of Nanocrystalline SnO(2) Obtained by Single Step Flame Spray Pyrolysis - Krivetskiy, Valeriy (Nanomaterials (Basel), 2019)
Improvement of sensitivity, lower detection limits, stability and reproducibility of semiconductor metal oxide gas sensor characteristics are required for their application in the fields of ecological monitoring, industrial safety, public security, express medical diagnostics, etc. Facile and scalable single step flame spray pyrolysis (FSP) synthesis of bimetal AuPd sensitized nanocrystalline SnO(2) is reported. The materials chemical composition, structure and morphology has been studied by XRD, XPS, HAADFSTEM, BET, ICP-MS techniques. Thermo-programmed reduction with hydrogen (TPR-H(2)) has been used for materials chemical reactivity characterization. Superior gas sensor response of bimetallic modified SnO(2) towards wide concentration range of reducing (CO, CH(4), C(3)H(8), H(2)S, NH(3)) and oxidizing (NO(2)) gases compared to pure and monometallic modified SnO(2) is reported for dry and humid gas detection conditions. The combination of facilitated oxygen molecule spillover on gold particles and electronic effect of Fermi level control by reoxidizing Pd-PdO clusters on SnO(2) surface is proposed to give rise to the observed enhanced gas sensor performance.